DIAGNOSING TELKOMSEL MOBILE REVENUE UNDERPERFORMANCE FOLLOWING FIXED-MOBILE CONVERGENCE INTEGRATION - Pingkan Reinne Ticoalu; Utomo Sarjono Putro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
In July 2023, Telkom merged the B2C business of IndiHome into Telkomsel, creating the largest Fixed-Mobile Convergence (FMC) operator in Indonesia and is expected to drive growth through convergence synergies. However, despite the increase in consolidated revenue after the merger, the performance of Telkomsel’s core mobile business was deteriorating. Mobile revenue fell, ARPU was flat and RPMB declined, even as the customer base expanded and data consumption grew. This study investigates whether the decline was caused by industry-wide circumstances or a company-specific execution gap. The analysis is based on a qualitative case study approach, using publicly available data from 2021-2024, combining PESTEL, Porter’s Five Forces, competitor benchmarking, revenue driver performance diagnostic, Marketing Mix analysis, Kepner-Tregoe Problem Analysis and Cause Mapping. The results show that the fall was mainly due to internal monetization problems rather than declining demand or network competitiveness. The three root causes were: Pricing strategy prioritizing traffic growth over value capture; Revenue dilution from OTT substitution and revenue sharing business scheme; and FMC monetization gap limiting synergy realization. The study concludes that recovery depends on monetization discipline, better execution of convergence and better capture of value from digital services, not pursuing new sources of competitive advantage.